Effects of corticosteroids on new-onset atrial fibrillation after cardiac surgery: A meta-analysis of randomized controlled trials. Issue 11 (19th March 2021) - Liu, Lu; Jing, Fu-Yu; Wang, Xiao-Wen; Li, Lin-Jun; Zhou, Rui-Qin; Zhang, Cheng; Wu, Qing-Chen
Abstract: Background: Postoperative atrial fibrillation (POAF) occurs commonly after cardiac surgery. Studies suggest that corticosteroid can reduce the incident of POAF. However, the results remain controversial. This meta-analysis aimed to evaluate the efficacy and safety corticosteroid on the prevention of POAF following cardiac surgery. Methods: Randomized controlled trials were identified through a systematic literature search. Two investigators independently searched articles, extracted data, and assessed the quality of included studies. Primary outcome was the incidence of POAF as well as length of hospital stay and intensive care unit stay, wound and other infection, mortality, duration of ventilation, myocardial infarction, gastrointestinal complications, high blood sugar, stroke, and postoperative bleeding. Results: Fourteen studies with 13, 803 patients were finally involved in the present study. Overall, corticosteroid significantly decreased the risk of POAF (relative risk [RR], 0.7; 95% confidence interval [CI], 0.55–0.89; P = .003). There were no significant differences in the incidence of length of intensive care unit stay (RR, −2.32; 95% CI, −5.44 to 0.80; P = .14) and hospital stay (RR, −0.43; 95% CI, −0.84 to −0.02; P = .04), infections (RR, 1.01; 95% CI, 0.83–1.23; P = .9), mortality (RR, 0.87; 95% CI, 0.71–1.06; P = .16), duration of ventilation (RR, −0.29; 95% CI, −0.65 to 0.07; P = .12), gastrointestinal complications (RR, 1.26; 95% CI, 0.91–1.76; P = .16), high blood sugar (RR, 1.98; 95% CI, 0.91–4.31; P = .09), stroke (RR, 0.9; 95% CI, 0.69–1.18; P = .45), postoperative bleeding (RR −44.54; 95% CI, −115.28 to 26.20; P = .22) and myocardial infarction (RR, 1.71; 95% CI, 0.96–1.43; P = .12). Conclusion: Our review suggests that the efficacy of corticosteroid might be beneficial to POAF development in patients undergoing cardiac surgery. The strength of this association remains uncertain because of statistical and clinical heterogeneity among the included studies. Abstract : Supplemental Digital Content is available in the text